دراسة واقعية لظاهرة الوحي يف الدراسات االستشراقية املنصفة - Abualyqa, Yousif Mousa Ali Abdalla (Penerbit Universiti Kebangsaan Malaysia, 2024)
The phenomenon of revelation is among the most critical subjects studied by Orientalists, as proving the occurrence of revelation leads to substantiating the authenticity of the Quran, the prophethood of Muhammad (peace be upon him), and confirming his message. Most Oriental scholars initially lacked conviction in the descent of revelation upon the Prophet (peace be upon him), as proving revelation validates his prophethood while denying it opposes this validation. This research raises questions about the concept of revelation, the biased stances of Orientalists towards revelation, the evidence they relied upon to deny the descent of revelation, and how fair Orientalists responded to those who rejected the phenomenon of revelation. The significance of this research lies in highlighting the danger posed by biased Orientalists who studied revelation, aiming to strip Prophet Muhammad (peace be upon him) of prophetic qualities. Therefore, the objective is to explore the opinions of some Orientalists regarding revelation, delineating both their negative and positive, as well as moderate, positions by tracing their methodologies and relied-upon means. To achieve this goal and others, this research utilizes descriptive and historical methods, identifying the research problem, gathering related facts and information, and specifying primary and secondary sources of these facts. These facts are then categorized, analyzed, their relationships identified, and results presented and interpreted. The most significant findings emphasize the necessity of proving revelation to Prophet Muhammad (peace be upon him), as it validates numerous aspects: the authenticity of the Quran, the prophethood of Muhammad (peace be upon him), and confirming his message.